Ship domain applied to determining distances for collision avoidance manoeuvres in give-way situations. (1st October 2018) - Szlapczynski, Rafal; Krata, Przemyslaw; Szlapczynska, Joanna
Abstract: Ship domain is often used in marine navigation and marine traffic engineering as a safety condition. The basic idea behind those applications is that an encounter of two or more ships can be considered safe if neither of ship domains is intruded by other ships. Research utilising this approach has been documented in numerous works, including publications on optimising collision avoidance manoeuvres performed to fulfil domain-based safety conditions. However, up to this point there has been no method, which would apply ship's domain to determine the last moment when a particular collision avoidance manoeuvre can still be successfully performed. This issue is addressed here. The proposed method uses a model of ship's dynamics to assess the time and distance necessary for a manoeuvre resulting in avoiding domain violations in give-way situations. The model and the method are described in detail and illustrated in a series of simulation results. The simulations cover full spectrum of typical give-way encounters in various circumstances: head-on, crossing and overtaking situations; manoeuvres limited to course alteration and those combining turns with speed reduction; open or confined waters and finally – in good and restricted visibility. Highlights: The method determines safe distance for ship evasive manoeuvres in give-way situations. Safe separation between ships is represented by a ship domain. A detailed modelling of ship dynamics is applied. Robust algorithms are used – the method is fast enough to work in real time. The results are action lines around the ship obtained for various encounter types.